A good instrument for the protection of credit that raises some practical problems: The european small claim procedure - Sigüenza López, Julio (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
This study analyzes the European small-amount process, an instrument which intendeds to favor the collection of cross-border credits not exceeding 5.000 euros which, despite its simplicity, or perhaps precisely because of it, presents many problems practical. It is based on standardized forms, without needing the intervention of legal professionals, thus being developed mainly in written. Nevertheless, it is foreseen the possibility is foreseen that the evidence can be practiced in a hearing through videoconference or other communication systems, even though it can call into question the guarantees inherent to orality, particularly that of immediacy. The fact that the sentence that puts an end to it can be executed directly in any State of the European Union that has signed Community Regulation 861/2007 is one of its main attractions, being necessary to enhance the other incentives whether a more effective use is desired.